PENGARUH STRUKTUR AKTIVA, UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL - Andika, Aries Prasetyo; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of assets structure, firm size, profitability and business risk to the capital structure of the banking companies which are listed in the IDX in 2011-2014 periods. In running the business, company has important aspects. One of the important aspects is financial aspectin which the financial aspect has important role about the decision making related to the capital of the company. The company can select the combination of right financing sources in order to be able to provide the optimal profit. The samplesare 14 banking companies which are listed in Indonesia Stock Exchange (IDX) and they have been selected by using purposive sampling technique. The analysis technique has been done by using multiple regressionsand classic assumption test which consists of normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test. Meanwhile the hypothesis test has been done by using goodness of fit test and t test with SPSS program 21 version. Based on this result of multiple regressions analysis with the significance level 5%, this research shows that the assets structure has negative influence to the capital structure; meanwhile firm size, profitability and business risk have positive influence to the capital structure.Keywords: profitability, firm size, business risk, assets structure capital structure.